Isolation Endophyte Bacteria from Keladi Merah (Caladium bicolor L.) as Activity Potential Antimicroba - Utami, Anggraini Putri; Khairillah, Yuyun Nisaul; Jagad, Nur Jati; Ramanda, Galih Dwiki (Jurnal Biologi Tropis, 2025)
Since endophytic bacteria are known to generate bioactive substances with possible antibacterial qualities, they present a viable substitute for antibiotics in the fight against antibiotic resistance, especially in harmful bacteria like Staphylococcus aureus. This study aimed to isolate and identify potential endophytic bacteria from red caladium plants (Caladium bicolor L.) and evaluate their antimicrobial activity against S. aureus, a Gram-positive bacterium notorious for its antibiotic resistance. The research was conducted using the disc diffusion method to assess the inhibitory effects of endophytic bacterial isolates on S. aureus growth. The results revealed varying levels of antimicrobial activity among the isolates, with isolate CLB242 demonstrating an average inhibition zone of 16.33 mm, isolate CLB244 showing an average of 17.6 mm, and isolate CLB245 showed an inhibition zone of 4 mm. Meanwhile, other isolates did not produce any inhibition zones, suggesting possible resistance or undetectable active compounds. Certain endophytic bacterial isolates from Caladium bicolor L. exhibit promising antimicrobial activity against S. aureus, highlighting their potential as sources of novel antimicrobial agents. Further research is recommended to identification of the active isolates molecular profiles and characterization of their bioactive compounds responsible for the observed antimicrobial effects, as well as to explore their mechanisms of action and potential applications in pharmaceutical development.